Priložnosti in izzivi kvantnih satelitskih komunikacij - Radaković, Katarina (Elektrotehniški vestnik, 2025)
Quantum communication via optical satellite links is a crucial step towards global secure communication networks. This paper provides a comprehensive overview of the opportunities and challenges associated with the implementation of quantum communication technologies over optical satellite links. We explore the potential of such systems for long-distance quantum key distribution (QKD), quantum entanglement distribution, and the construction of global quantum networks that overcome the limitations of terrestrial fiber-based systems. The unique properties of optical satellite links, including their ability to span long distances with minimal signal loss, offer promising opportunities for robust quantum communications. However, there are significant technical and environmental challenges to realizing these systems, including atmospheric turbulence, beam tracking and pointing, and photon loss. In addition, we address the need for international cooperation, standardization and regulatory frameworks to ensure seamless integration into the existing communications infrastructure. By analyzing recent experimental demonstrations and theoretical developments, this paper highlights the crucial milestones that have been achieved and identifies key areas for future research. Our findings highlight the transformative potential of satellite-based quantum communications and its role in shaping the next generation of secure communication systems.
Keywords: cybersecurity; kibernetska varnost; kvantna komunikacija; kvantna tehnologija; kvantno razdeljevanje ključev; quantum communication; quantum key distribution; quantum technology; satelitska komunikacija; satellite communication; telecommunications; telekomunikacije